Epidemiologic Study of 284 Patients with Urogenital Trauma in Three Trauma Center in Tehran - Salimi, Javad; Nikoobakht, Mohammad Reza; Zareei, M R (Urology Journal, 2009)
Purpose: To perform an epidemiologic study of urogenital injuries in traumatic patients who were referred to three traumatic centers in Tehran during one year. Materials and Methods: This study included a part of data of National Trauma Registries, which was performed within one year. Questionnaires were completed by trained staff in three different geographical regions of Tehran: Shohada-e-Tajrish hospital (north of Tehran), Sina hospital (south of Tehran), and Shaheed Faiazbakhsh (west of Tehran). Results: Two hundred and eighty four (5%) out of 57367 patients who were referred to the above mentioned centers had genitourinary trauma, of whom, 145(42%) were hospitalized. Males with a frequency of 92% (258 patients) were the most injured group. Patients mean age was 25 Â± 14 years, mostly between 20 and 29 years (33.6%) followed by 10-19 years age group with a frequency of 25.6%. Non-penetrating trauma with a frequency of 96% was the most common type and accident was the most mechanism of trauma. One hundred and one patients out of the studied population had associated injuries. The most frequent injuries were occurred in extremities (40%) and the less in head and neck (7%). There were 22 (21.7%) intra-abdominal organ injuries. Sixty nine percent of patients developed mild injury (ISS < 7), 20% developed severe injury and (ISS > 12), and 4.2% of patients died. The most common injured organ was kidney (3.3%) and the least one was ureter, as no ureteral injury was reported. Conclusion: Although a low percentage of traumatic patients develop urogenital injuries, disregarding these injuries may lead to serious complications and it is recommended to consider these injuries while dealing with such patients. Considering the fact that these complications which could be preventable, are mostly developed in the youth, making solution for such problem is recommended.